Rancang Bangun Aplikasi Monitoring Pengamanan Area Objek Vital Berbasis Android - Oktarino, Ade; Rohayani, Hetty (UNIVED Press, 2019)
The use of the Jambi Regional Police's Vital Object Security Monitoring Application is useful for monitoring the evaluation of vital objects in the Jambi Regional Police's jurisdiction in order to detect early incidents at the location in order to improve Kambtibmas (Public Order Security). This Android-based application is very easy to use and reporting from the security guard at PT PLN Dalkit uses visuals in the form of photos and videos which can be directly monitored in real time. PT PLN Dalkit Jambi is one of the power plants that supplies electricity in the province Jambi and is one of the Vital Objects recorded by the Jambi Regional Police, for this reason it requires quite serious supervision under the Security of Vital Objects of the Jambi Regional Police. This research uses a system modeling method using UML (Unified Modeling Language).